Problems Of Improving The Creative Competence Of Future Chemistry Teachers (Eurasian Scientific Herald, 2024)
The article provides a description of the pedagogical competencies of a chemistry teacher, which are components of professional readiness for organizing educational and research activities of students in general education organizations.